2019
DOI: 10.1186/s13018-019-1363-y
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular platelet-rich plasma injection for knee osteoarthritis: a summary of meta-analyses

Abstract: Objective: The purpose of this study was (1) to perform a summary of meta-analyses comparing platelet-rich plasma (PRP) injection with hyaluronic acid (HA) and placebo injection for KOA patients, (2) to determine which meta-analysis provides the best available evidence to making proposals for the use of PRP in the treatment of KOA patients, and (3) to highlight gaps in the literature that require future investigation. Material and methods: PubMed, EMBASE, and Cochrane databases search were performed for meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 58 publications
0
42
0
4
Order By: Relevance
“…In recent years, there have been an increasing number of studies on the application of intraarticular injection of platelet-rich plasma (PRP) or hyaluronic acid (HA) in the treatment of KOA. Many systematic reviews suggest that intra-articular injection of PRP, compared to HA, can alleviate pain symptoms and improve knee function in patients with KOA [6,8,9]. However, a double-blind randomized controlled trial with a 5-year follow-up showed that the combination of HA and PRP improved pain and function in patients with a history of chronic symptomatic knee degenerative changes and osteoarthritis [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been an increasing number of studies on the application of intraarticular injection of platelet-rich plasma (PRP) or hyaluronic acid (HA) in the treatment of KOA. Many systematic reviews suggest that intra-articular injection of PRP, compared to HA, can alleviate pain symptoms and improve knee function in patients with KOA [6,8,9]. However, a double-blind randomized controlled trial with a 5-year follow-up showed that the combination of HA and PRP improved pain and function in patients with a history of chronic symptomatic knee degenerative changes and osteoarthritis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a musculoskeletal disease characterized by synovial inflammation, progressive cartilage wear, and subchondral bone hyperplasia [1,2]. It was reported that OA is one of the top ten causes of lower limb disability [3,4]. For many years, cartilage damage has been considered to be the main pathogenesis of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Injections of intra-articular hyaluronic acid (HA) and platelet-rich plasma (PRP) are used as other non-surgical treatment options for the patients with KOA [11]. HA, a high-molecular weight glucosamine, is generated by chondrocytes, synoviocytes, and fibroblasts and responsible for the viscoelasticity and lubrication of the knee joint [12]. It is shown that HA concentrations in osteoarthritic knees have been reduced.…”
Section: Introductionmentioning
confidence: 99%